KONSEP PEMBANGUNAN TATA RUANG, INFRASTRUKTUR, SUMBERDAYA ALAM DAN LINGKUNGAN (SUATU STUDI WILAYAH PERKOTAAN) - Anhar Drakel (Jurnal Pendidikan dan Ekonomi (JUPEK), 2021)
Urban infrastructure development has a very significant role in the successful use of urban space. The basic concept of development planning in spatial planning must be oriented to the fulfillment of urban infrastructure services that are able to support the realization of a safe, orderly, smooth, beautiful and healthy urban development pattern that is oriented towards the concept of resources and the concept of the environment. The concept of regional spatial planning development planning, infrastructure, natural resources and the environment must meet the elements in the development concept, namely spatial planning, regional planning, structuring slums, illegal buildings and settlements, the need and availability of livable houses, housing and residential environments. , flood management and management, city cleanliness, provision of affordable housing for the poor, sea, land and air development infrastructure, green open space, underground water control, control of Group C mining of minerals, control of environmental pollution, law enforcement.